(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Around 1 in 400–5000 live births of females result in vaginal agenesis, a malformation of the female genital tracts. Using an amnion graft to treat vaginal agenesis is a straightforward, widely accessible, economically advantageous, and physiological surgery that leaves no additional scars on the body. This study sought to ascertain whether individuals with vaginal agenesis may successfully undergo laparoscopic-assisted vaginoplasty utilising amnion as a transplant to create a neovagina. Methods:Ten cases of vaginal agenesis linked to Mayor-Rokitansky-Kuster-Hauser (MRKH) Syndrome were included in this case series and were hospitalised within a year. The ladies with MRKH condition were either previously married or unable to consummate their marriage due to a blind vagina when they were brought for surgical intervention. To maintain the patency of the neo-vagina, a laparoscopically guided vaginoplasty was carried out as part of the care. Results:In all but one of the patients, laparoscopy-guided vaginoplasty with an amnion graft was effective. The procedure was stopped when the rectum was hurt, and the harm to the rectum was repaired. Except for one example, the functional outcomes of the neovagina were quite good. None experienced any major postoperative problems. The patients were happy with the postoperative results. Also, the neovagina was psychologically acceptable and sufficiently patent for sexual function. Conclusion: Over the past few years, the new vaginoplasty technique has developed. The most common practice, however, is a laparoscopic approach using several graft materials. A safe and efficient method for treating MRKH syndrome patients with vaginal agenesis is vaginoplasty with amnion grafts. J Bangladesh Coll Phys Surg 2023; 41: 177-182